6-benzylaminopurine induces somatic embryogenesis in the staminodia of new genotypes of Theobroma cacao L. from the Papaloapan Basin of Mexico and differs from that of T. bicolor Bonpl. - Martínez-Hernández, Nancy Carmín; Dávila-Figueroa, Carlos Antonio; Morales-Serna, José Antonio; Castro Cerritos, Karla Viridiana; Martínez Galero, Nelda Xanath; López Arjona, Héctor; Villalobos Amador, Enrique (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
Theobroma cacao and T. bicolor are among the most important agricultural crops of the Mexican tropics. Currently, in Mexico, the propagation of these crops is performed via seeds, which indicates that demand exceeds production. In this context, somatic embryogenesis (SE) is an alternative to this approach. Thus, we evaluated the presence of embryogenic genotypes of T. cacao and T. bicolor in the Papaloapan Basin of Mexico with the idea of implementing this technology in the region. The analysis of the phenotypic expression of the floral whorls demonstrated that, unlike T. bicolor, the combination of 6-benzylaminopurine and 2,4-dichlorophenoxyacetic acid induces different morphogenetic responses in the genotypes that were evaluated in the primary callus phase of T. cacao. Staminodia presented with the highest percentage of caulogenesis in T. cacao, whereas T. bicolor presented with the highest frequency of caulogenesis in Staminodia and carpels. Some calli differentiated in the roots to a greater extent than those derived from the staminodes of T. cacao. The calli of T. bicolor did not differentiate. A parallel study using thidiazuron as an inducer demonstrated similar results for calli of both species; however, rhizogenesis from staminodes was 50% lower for the evaluated genotypes of T. cacao. Staminodes were the only structures that demonstrated primary somatic embryogenesis (PSE) in 66% of the T. cacao genotypes that were evaluated by using benzylaminopurine. Finally, secondary somatic embryogenesis (SSE) was evaluated in cotyledons and reached a 60% success rate, of which 95.48% were normal somatic embryos. Both types of embryogenesis were morphologically characterized using optical and/or scanning electron microscopy.
Keywords: Cacao; Embriogénesis somática; Tidiazurón